2013
DOI: 10.1016/j.physletb.2013.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical realizations of l-conformal Newton–Hooke group

Abstract: The method of nonlinear realizations and the technique previously developed in [Nucl. Phys. B 866 (2013) 212] are used to construct a dynamical system without higher derivative terms, which holds invariant under the l-conformal Newton-Hooke group. A configuration space of the model involves coordinates, which parametrize a particle moving in d spatial dimensions and a conformal mode, which gives rise to an effective external field. The dynamical system describes a generalized multi-dimensional oscillator, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 47 publications
(159 reference statements)
2
55
0
Order By: Relevance
“…In a series of papers [9,10,11,12,13] it was shown that the Pais-Uhlenbeck oscillators are invariant under the ℓ = 1 2 +N 0 CGAs. These systems, however, unlike the ℓ-oscillator (1), are defined by higher-derivatives equations.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of papers [9,10,11,12,13] it was shown that the Pais-Uhlenbeck oscillators are invariant under the ℓ = 1 2 +N 0 CGAs. These systems, however, unlike the ℓ-oscillator (1), are defined by higher-derivatives equations.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain NH counterpart of the model (16), it follows to apply Niederer's coordinate transformation of the form…”
Section: Higher-derivative Analogue Of Many-body Conformal Mechanicsmentioning
confidence: 99%
“…Recently, symmetries of these higher-derivative models have been extensively studied 13,14,[16][17][18][19][20][21][22][23] . In particular it has been shown that the l-conformal Galilei group is the maximal symmetry group of the free (2l + 1)-order particle 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 First, dynamical realizations of these algebras constructed so far did not assign any clear physical meaning to the parameter l. Second, apart from the oscillator-like models coupled to external field [4][5][6], no interacting theory which exhibits such symmetries is known. Third, because a number of functionally independent integrals of motion needed to integrate a differential equation correlates with its order, dynamical realizations of the l-conformal Galilei/Newton-Hooke algebra in general involve higher derivative terms (see, e.g., [7][8][9][10][11][12][13] and the references therein).…”
Section: Introductionmentioning
confidence: 97%